Low mortality rate in Italian rheumatoid arthritis patients from a tertiary center: putative implication of a low anti-carbamylated protein antibodies prevalence - Iacono, Daniela (Open Access Rheumatol, 2018)
BACKGROUND AND OBJECTIVE: Anti-carbamylated protein antibodies (anti-CarP Ab) represent a novel kind of autoantibodies specificity detectable in the sera of patients with rheumatoid arthritis (RA). They have been recently reported to be associated with increased mortality in Spanish patients with RA. The aim of our study was to compare the incidence mortality rates (IMRs) detected in RA patients from a tertiary Italian center with those reported in other European tertiary centers and to evaluate the putative role of anti-CarP Ab in modulating the low IMR detected in our patients. METHODS: Clinical charts of patients consecutively admitted to our center, from January 1, 2008, to December 31, 2014, were retrospectively reviewed. The mortality rate (expressed as the number of deaths in the cohort divided by the number of years of IMR follow-up) and causes of death were assessed at December 31, 2015. Sera of 61 patients, representative of the whole cohort, collected at the time of admission to our center were investigated for the presence and the level of anti-CarP Ab. Demographic and clinical features, mortality rates and prevalence of anti-CarP Ab in our series were compared with those reported in other European cohorts. RESULTS: We observed 608 patients for a median of 3.51 years. All-cause and cause-specific IMRs in our cohort were significantly lower than the Better Anti-rheumatic Farmaco-therapy and the Spanish cohort, while only all-cause and cardiovascular IMRs were significantly lower in our series with respect to the Leiden Early Arthritis Clinic cohort. Anti-CarP Ab prevalence was significantly lower in our series than in any other European cohorts. CONCLUSION: We confirm that the mortality rate is lower in our Italian RA cohort with respect to other European cohorts. Whether the low prevalence of anti-CarP Ab might be responsible for this result awaits to be furtherly investigated.